Analysis of the research results of the zeolite drying process - Marchevsky Viсtor; Novokhat, Oleh; Margarian, Artem (Technology audit and production reserves, 2018)
The object of research is the zeolite drying process by radiation method. Loose zeolite of two fractions (0–1 mm and 0–5 mm) are used as prototypes. Drying occurs at a layer thickness of zeolite equal to 3 and 5 mm. According to the source of thermal energy, an electric infrared emitter of ceramic type with a nominal electric power of 1 kW is used. The influence of the zeolite fractions, the thickness of the zeolite layer during drying, and the heat flux density on the kinetics of the drying process is established. The numerical values of the zeolite drying time in different periods of drying are determined. According to the analysis of the research results of zeolite drying by a radiation method, it is established that the kinetic laws of this process are similar to the process of drying capillary-porous bodies. The duration of the drying periods depends on the heat flux density and decreases with increasing heat flux density. An increase in the value of the zeolite fractions intensifies the drying process in the warm-up periods and the first drying period, but does not affect the drying rate in the second period. Also a certain influence of the drying process parameters on the moisture content at the end of the first period. The temperature of the zeolite in the first period of drying is not constant, but increases. This indicates an excess of thermal energy supplied during this period. Analysis of the research results also shows that the drying time of the zeolite fraction 0–5 mm is less than the fraction 0–1 mm. Therefore, it is advisable to dry the zeolite fraction of 0–5 mm and, if necessary, further grind after the drying process. This will reduce energy costs and production time of the zeolite as a whole. The obtained curves of zeolite drying allow to predict the nature of the process and can be used to design drying plants.